Anticipating the Challenging and Unpredictable Long Term Cardiovascular Effects of COVID-19: A Review - Rahman, Mohammad Arifur; Rahman, Afzalur; Ahmed, Mohsin; Islam, AKM Monwarul; Islam, Md Mesbahul; Mahmod, Muhammad Salim; Ahmad, Tanveer (Bangladesh Heart Journal, 2021)
Abstract not available Bangladesh Heart Journal 2020; 35(2) : 147-154